OTOMATISASI SISTEM WATER TREATMENT PLANT BERBASIS MIKROKONTROLER UNTUK PENGENDALIAN PROSES PENGOLAHAN DAN PEMANTAUAN KUALITAS AIR SUMUR - Azzahiru, Muhammad Zaky Reihan; Hadianto, Rahmadani (Jurnal Mahasiswa Terapan; Vol 1 No 3 (2025): Jurnal Mahasiswa Terapan, 2025)
Water Treatment Plant (WTP) has several stages of processing processes such as intake, coagulation, flocculation, sedimentation, filtration and reservoir. This process relies on pumps that are operated manually, but this affects the quality of the water produced to be less than optimal. To handle problems that arise in the previous water treatment system, a microcontroller was used as the system which aims to control the system automatically and maximize the quality results of water treatment. By controlling the actuator, it is also based on the accuracy of drug filling, the precision of the quality sensors used and the total time the system runs consistently. The value obtained was that the control accuracy of the drug filling pump actuator reached 90% and 100% which met the regulatory requirements, the pH and turbidity values during testing met the specified minimum and maximum limit requirements with low deviation values which prove that the tool has high precision, control of all actuators and sensor readings that work well with time consistency.